Emergency department ultrasound (EDU): clinical adjunct or plaything?. Issue 5 (20th April 2005) - McLaughlin, R; Collum, N; McGovern, S; Martyn, C; Bowra, J
Abstract : Background: Emergency department ultrasound (EDU) is a physician performed ultrasound service aimed at improving patient flow and diagnosis in the emergency department. Methods: This paper describes the initial phase of the introduction of EDU with three illustrative case reports and a discussion on the pitfalls and benefits of EDU. Results and discussion: In three cases discussed here, the use of EDU facilitated treatment and reduced the need for formal radiological scanning. While there are drawbacks to EDU, we believe these are far outweighed by the advantages, and in a recent survey of emergency medicine consultants throughout Ireland, the vast majority were in favour of its introduction. Conclusion: EDU has become a routine part of our clinical practice, and although we are still on a learning curve with regard to its use, we have experienced significant benefits in patient care. With technological advances (such as improved image resolution and teleradiology) the potential for EDU will continue to expand, but training, practice, accreditation, and audit are essential.